1986
DOI: 10.2172/6201667
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Leach Test(s) Program: Annual report

Abstract: LIST OF FIGURES Figure No. Page 3.1 Compositional phase diagram for the solidification of aqueous waste containing 50 wt% or less ^SQ, with portland type I cement 8 3.2 Ternary compositional phase diagram for the solidification of incinerator ash in portland type I cement 8 3.3 Sodium ion concentrations released from vinyl ester-styrene/sodiurn sulfate waste forms after 3 day immersion in deionized water at 20°C versus waste loading 10 4.1 Cumulative fraction releases from portland cement for Sr-85 and Cs-137.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Guilt has been researched in a number of disciplines, including philosophy (Johnson & Johnson, 1977), theology (Izard, 1977), and psychology (Dougherty, 1986; Plutchik, 1980; Wicker, Payne, & Morgan, 1983). Much of this research has suggested guilt results from “essentially private recognition that one has violated a personal standard” (Kugler & Jones, 1992, p. 318).…”
Section: Guilt and Guilt Appealsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guilt has been researched in a number of disciplines, including philosophy (Johnson & Johnson, 1977), theology (Izard, 1977), and psychology (Dougherty, 1986; Plutchik, 1980; Wicker, Payne, & Morgan, 1983). Much of this research has suggested guilt results from “essentially private recognition that one has violated a personal standard” (Kugler & Jones, 1992, p. 318).…”
Section: Guilt and Guilt Appealsmentioning
confidence: 99%
“…Similarly, manufacturers of household and children's products have used guilt appeals targeted at working mothers. Although there is evidence of the increased use of guilt appeals to induce purchasing of products, most advertising and consumer research regarding guilt appeals has been conducted in the context of changing behaviors, volunteerism, and charitable contributions (Bozinoff & Ghingold, 1983; Dougherty, 1986).…”
mentioning
confidence: 99%
“…Bitumen is finding increased application in the waste management field (Sn ell man and Uotila, 1984;Dougherty et al, 1986;Mattus and Kaezmarsky, 1987). Experiments indicate that radionuclides leach less from bitumen than from concrete.…”
Section: Solidificationmentioning
confidence: 99%
“…Various polymers could be appropriate as solidifying agents (Franz and Colombo, 1985;Dougherty et al, 1986;Nielson et al, 1987). Their overall suitability is based on low permeability to water, high plasticity, and favorable economics.…”
Section: Solidificationmentioning
confidence: 99%
See 1 more Smart Citation